Characterizing Hypervascular and Hypovascular Metastases and Normal Bone Marrow of the Spine Using Dynamic Contrast-Enhanced MR Imaging - Khadem, N.R.; Karimi, S.; Peck, K.K.; Yamada, Y.; Lis, E.; Lyo, J.; Bilsky, M.; Vargas, H.A.; Holodny, A.I. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The role of DCE-MR imaging in the study of bone marrow perfusion is only partially developed, though potential applications for routine use in the clinical setting are beginning to be described. We hypothesize that DCE-MR imaging can be used to discriminate between hypervascular and hypovascular metastases based on measured perfusion variables. MATERIALS AND METHODS: We conducted a retrospective study of 26 patients using conventional MR imaging and DCE-MR imaging. Patients were assigned to a hypervascular or hypovascular group based on tumor pathology. ROIs were drawn around normal-appearing bone marrow (internal controls) and enhancing tumor areas. Average wash-in enhancement slope, average peak enhancement signal percentage change, and average peak enhancement signal percentage change in areas of highest wash-in enhancement slope were calculated. Indices were compared among control, hypervascular, and hypovascular groups. Conventional imaging was assessed by calculating pre- to postgadolinium signal percentage changes in hypervascular and hypovascular lesions. RESULTS: Hypervascular and hypovascular tumors differed significantly with regard to wash-in enhancement slope (P < .01; hypervascular 95% CI, 22.5–26.5 AU/s; hypovascular 95% CI, 14.1–20.9 AU/s) and peak enhancement signal percentage change in areas of highest wash-in enhancement slope (P < .01; hypervascular 95% CI, 174.1–323.3%; hypovascular 95% CI, 39.5–150.5%). Peak enhancement signal percentage change over all voxels was not significant (P = .62). Areas of normal-appearing marrow showed no appreciable contrast enhancement. Conventional contrast-enhanced MR imaging was unable to differentiate between hypervascular and hypovascular tumors (P = .58). CONCLUSIONS: Our data demonstrate that, unlike conventional MR imaging sequences, DCE-MR imaging may be a more accurate technique in discriminating hypervascular from hypovascular spinal metastases. CIconfidence intervalDCEdynamic contrast-enhancedSEstandard errorSIsignal intensitysignalbasebaseline valuesignalmaxmaximum signal intensitySTIRshort τ inversion recoverytimerisecontrast enhancement rise timeTICtime intensity curve